Communication conflicts among mobility students at the International Division Universiti Putra Malaysia - Roslan, Nur Maisarah; Abdul Halim, Hazlina (Penerbit Universiti Malaysia Terengganu, 2016)
This study focuses on the conflict in communication among mobility students at Universiti Putra Malaysia (UPM). The objectives of the study were to identify and discuss the conflict in communication by using Stubbs's (1983) discourse analysis theory. 10 subjects from China participated in the study. The subjects were interviewed based on their experience in dealing with the staffs at the International Division, Universiti Putra Malaysia. Six characteristics of discourse analysis were found and analyzed. The results revealed that all ten subjects were having conflict in communication during their stay at UPM. They faced conflict in understanding accent and choice of words. They also experienced confusion and misunderstanding. It is hoped that the findings from this research will serve as a comparison to compare the conflicts with other students from other countries in a future study.